Healthy food and human body - Berezovska, Olga (My University, 2014)
People all over the world try to follow the "fashion" on healthy food and healthy diet. The perception of the importance of right nutrition and right food is increasing day by day. Everybody understands that the benefits of healthy eating are unique. They are far-reaching health advantages and gains that cannot be overlooked or quantified.
Keywords: здорова їжа; здорове харчування; healthy food; fashion; кафедра ділової іноземної мови та міжнародної комунікації